Hepatitis B infection among indigenous people in Nepal: looking through an equity lens - Shedain, Purusotam Raj; Baral, Gehanath; Maharjan, Basant (Nepal Journal of Obstetrics and Gynaecology, 2018)
Background: Disparity in health care service and disease prevalence are global issues. Hepatitis B infection is a global public health problem; its prevalence is ubiquitous and heterogeneous. This article reviews the situation and an impact of hepatitis B infection in the indigenous people in Nepal through the lens of equity perspective. Methods: Literature search and collection of information from different sources. Results: Hepatitis B prevalence is low (0.9%) at the country level in Nepal but higher, up to 38%, among the indigenous population compared to the national prevalence. Those who live in the high endemic areas are at risk of getting the infection from both vertical and horizontal mode of transmission. The unvaccinated cohort of infant (0-11 months) between 2003 and 2016 has swollen, 2764362 in number or 29 % of the total cohort. The National Immunization Program (NIP) administered hepatitis B vaccination at 6 weeks of birth, considering the low prevalence at the national level. The NIP does not prevent perinatal transmission of the infection. The mother to child transmission of the infection often leads to chronic liver diseases and about 20–30% of adults who are chronically infected will develop cirrhosis and/or liver cancer. The indigenous populations are thus disproportionately affected by the infection. Conclusions: The policy update is required to implement the hepatitis B vaccination at birth or within 24 hours in high endemic setting along with a comprehensive package to reduce the disparity, prevent the transmission, risk of chronic infection and its sequelae to achieve the national goal and international commitment on the sustainable development goal by 2030.